Spherulites : evidence of herding strategies at Mapungubwe - Mashimbye, Prudence Myra (My University, 2013)
Agropastoralists during the Iron Age established their settlements in the Limpopo Valley to take advantage of the rich floodplains of the Shashe-Limpopo confluence. Trade in ivory may have been a draw card in the earlier Zhizo period (AD 900), but good climate and increased rainfall helped to maintain a growing population which in turn contributed to the rise of complex society and the first state in southern Africa, i.e. Mapungubwe (AD 1250-1300). The population increase and the concomitant agricultural land use, together with several droughts, would have challenged livestock management. Using carbon signatures, J. Smith (2005) discovered that cattle were sustained on graze alone, indicating sufficient grass in the valley for pasture during the Iron Age. I have used spherulites found in cattle dung to investigate the use of the confluence vlei area. Vlei grass would have provided extra pasturage. I considered time and space to interpret samples. For the Zhizo and Leokwe periods, I examined 13 samples, including Castle Rock, of which six were positive. K2 had nine positive samples out of 17 while Transitional K2 had 20 positives samples. The TK2 results suggest there was a greater need for extra pasturage associated with drought from AD 1220 to 1250. The Mapungubwe period is represented by 11 samples and five yielded positive results while the Khami period yielded 12 positive results out of 26 samples. These results show a regular use of the confluence vlei during the Iron Age associated with dry conditions.
Archaeology MSc Dissertation School of Geography, Archaeology and Environmental Studies Faculty of Science University of the Witwatersrand Johannesburg 2013
Keywords: Mapungubwe Site (South Africa); Excavations (Archaeology) - South Africa - Northern Province.; Iron age - South Africa - Mapungubwe.